O desenvolvimento político concebido a partir dos conceitos de governança política, capital político e autogoverno: análise dos impactos da atuação do SEBRAE no desenvolvimento político goiano de 2004 a 2011 - Oliveira Júnior, José Amorim de (2011)
This thesis analyses the political nature inherent to the development work done by Sebrae s working system. The research establishes a dialogue between philosophy and political sociology, resulting in the creating a political development definition, from the concepts of Political governance (increase of the public spaces of power; power as a key element of the Policy; associacionism and contesting), political capital (the importance of trust to build social capital; political recruitment and political inclusion: formation of new political leaders) and autogovern (empowerment; protagonism and responsiveness). We also analyse the performance of Sebrae in the area of public politics and its Sebrae s reposture as an agent of local and sectorial development, factors that consolidate its institutional role and corroborate the hypothesis of the research about the implications of the acting of this institution in the political development.